EFFECT OF RUBBER PRODUCTION, DOLLAR EXCHANGE RATE AND INFLATION ON RUBBER EXPORTS IN INDONESIA - Fatahillah Fatahillah; Devi Andriyani; Mutia Rahmah; Syarifah Syafira (LPPM Universitas Malikussaleh, 2022)
This study was conducted in Indonesia and aimed to examine the effect of rubber production, the dollar exchange rate, and inflation on rubber exports. The data analysis method used was multiple linear regression. The results showed that rubber production and inflation positively and significantly influenced rubber exports, while the dollar exchange rate negatively and significantly influenced rubber exports. Simultaneously, rubber production, the dollar exchange rate, and inflation positively and significantly influenced rubber exports in Indonesia, and the magnitude (R^2) of the effect of the amount of production, dollar exchange rate, and inflation on rubber exports was 0.5979 (59.79%)